2007
DOI: 10.2341/06-77
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sonic and Ultrasonic Scaling on the Surface Roughness of Tooth-colored Restorative Materials for Cervical Lesions

Abstract: This study investigated the effects of sonic and ultrasonic scaling on the surface roughness of five commonly used tooth-colored restorative materials for Class V cavities, including a flowable resin composite (Tetric Flow), a compomer (Compoglass F), a glass ionomer (Fuji II), a resin-modified glass ionomer (Fuji II LC Imp) and a resin composite (Z100). Twenty rectangular block specimens (16 x 6 x 1.5 mm) of each material were cured against matrix strips, then stored in artificial saliva for two months before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…Furthermore, the possibility of the abrasion of filler phase of resin materials by powder components of APD has been reported (3). The surface roughness of the giomer specimens treated with all prophylaxis methods was greater than 0.2 µm, which is a threshold value for bacterial adherence (14). Therefore, re-polishing of giomer restorations subsequent to the prophylaxis treatments tested might be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the possibility of the abrasion of filler phase of resin materials by powder components of APD has been reported (3). The surface roughness of the giomer specimens treated with all prophylaxis methods was greater than 0.2 µm, which is a threshold value for bacterial adherence (14). Therefore, re-polishing of giomer restorations subsequent to the prophylaxis treatments tested might be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Yap et al (3) reported that in flowable, minifill and polyacid modified composites, the control group (untreated) showed the lowest surface roughness compared to the groups with different prophylaxis methods. Furthermore, previous studies have shown that the surface roughness of restorative materials significantly increases following the use of prophylactic polishing pastes, tooth brushing and sonic and ultrasonic periodontal instruments (14,16,17). Giomer is a biphasic restorative material and each of the phases differs in hardness values with no uniform abrasion (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the size of the asperities seen with 5 FFMGIC was smaller than those on GIC and 1 FFMGIC samples. The increase in surface roughness of 5 FFMGIC could be due to the high density of the fibres and the formation of more homogenous bi -phasic material with a uniform distribution of the fibres within the structure [33] . The bi -phasic structure of FFMGIC was confirmed by skewed distribution of stiffness and topography.…”
Section: Surface Topography and Mechanical Propertiesmentioning
confidence: 99%
“…6 In cervical lesions, various restorative materials can be inserted, such as amalgam, composite resin, and glass ionomer, which can be affected by application of scalers. 14 The use of glass ionomer cements has increased since their introduction in the 1970s, because they have many characteristics of an ideal restorative material, such as similarity to tooth color, uniting with tooth structure, radiopacity, releasing fluoride over time, inhibiting demineralization, tissue compatibility, and contributing remineralization of adjacent dentin. [15][16][17][18] Furthermore, they are the most used filling material for minimally invasive restorations.…”
Section: 5005/jp-journals-10024-2061mentioning
confidence: 99%